Common Auditors in Supply Chain Relationships and the Provision of Trade Credit - Lisic, Ling Lei; Liu, Qiliang; Seidel, Timothy A.; Shi, Hanzhong; Wang, Angie; Zimmerman, Aleksandra (The Accounting Review, 2026)
ABSTRACT This study examines the association between a shared common auditor among suppliers and customers and trade credit. Using hand-collected pairwise trade credit data, we find that a supplier extends more trade credit to a customer audited by a common auditor. This association is robust to alternative design specifications and various sample restrictions to alleviate selection bias. We then interview trade credit managers and executives as a prelude to archival analyses exploring multiple potential mechanisms to explain this association. The collective results are most consistent with the explanation that mutual third parties to a dyadic relationship can foster trust through social connections and increased salience of reputation effects rather than that a common auditor reduces information asymmetry about the rigor of the audit process. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M41; M42.